Understanding the Social and Emotional Dimensions of HIV Self-Management: A Qualitative Study of Newly Diagnosed People Living With HIV in Queensland, Australia. (13th March 2022) - Hollingdrake, Olivia; Dean, Judith; Mutch, Allyson; Lui, Chi-Wai; Howard, Chris; Fitzgerald, Lisa
Abstract: Understanding of HIV self-management increasingly focuses on treatment adherence and associated health-related behaviors, yet people living with HIV (PLWH) seldom perform these actions in a social vacuum. Thus, delivering comprehensive self-management support programs for PLWH requires an understanding of the social and emotional dimensions of HIV self-management. Through thematic analysis of in-depth interviews with 35 newly diagnosed PLWH, this descriptive qualitative study highlights these dimensions and their effect on experiences of HIV diagnosis and care. HIV self-management involves interpersonal interactions that affect efforts to seek support and reimagine one's personal identity in a changed reality. Managing disclosures and navigating stigma constitute everyday work for many PLWH. Because stigma continues to impede care engagement and well-being for PLWH, health practitioners must extend focus beyond viral suppression and prioritize support for emotional and social self-management. Nurses can create safe, nonstigmatizing spaces for conversations about HIV, uphold the rights of PLWH around disclosure, and ensure that PLWH are connected to peer support services.